Prevalence and correlates of microalbuminuria in high-risk persons with hypertension, diabetes, or HIV at a tertiary hospital in Zambia. - Luyando Mutelo; Cornelius Simutanda; Lweendo Muchaili; Bislom C Mweene; Situmbeko Liweleya; Sydney Mulamfu; Gift C Chama; Lukundo Siame; Benson M Hamooya; Sepiso K Masenga (PLoS ONE, 2025)
Background Microalbuminuria is a critical marker for early kidney damage and a predictor for proteinuria, a defining feature of renal disease. Its detection in high-risk individuals is vital for reducing the risk of adverse renal outcomes, particularly among persons living with diabetes, hypertension, and HIV. The evaluation of microalbuminuria in high-risk individuals allows for the early detection of renal impairment and the assessment of cardiovascular risk profiles. Additionally, it informs targeted therapeutic interventions and provides critical prognostic information, thereby enhancing overall clinical outcomes. The goal of the study was to determine the prevalence and correlates of microalbuminuria in high risk patients. Methods A cross-sectional study was conducted at Livingstone University Teaching Hospital (LUTH) from September 2023 to July 2024. We employed homogeneous purposive sampling to recruit 306 high-risk adults (≥18 years) with diabetes, hypertension, and/or HIV. Purposive sampling was employed to recruit patients attending routine medical clinic at LUTH. Sample size was calculated using the formula for a single proportion (expected prevalence: 30%, margin of error: 5%, 95% CI), yielding 323; we recruited 306 due to logistical constraints. Data were collected directly from participants as well as using hospital records and laboratory analysis of blood/urine samples. Descriptive and inferential statistics were analyzed using SPSS v22. Results A total of 306 high-risk individuals were screened, with a median age of 46 years (IQR: 31-58). Of these, 61.8% (n = 189) were females and 38.2% (n = 117) were males. The prevalence of microalbuminuria was 28.8% (95%CI 23.7-33.8), while its prevalence among individuals with diabetes, hypertension, and HIV was 45.4%, 33.3%, and 39.1%, respectively. Microalbuminuria was significantly associated with diabetes (p = 0.033), individuals living with HIV (p = 0.035), and high-sensitivity C-reactive protein (Hs-CRP) (p = 0.007) in univariate analysis. On multivariable analysis, microalbuminuria was associated with diabetes (AOR 2.90; 95% CI 1.02-8.19 p = 0.044), Living with HIV (AOR 1.96; 95%CI 1.02-3.78; p = 0.042) and Hs-CRP (AOR 1.16; 95%CI 1.02-1.30 p = 0.015). Conclusion The findings underscore the importance of routine screening for microalbuminuria in high-risk populations. Early detection and intervention could prevent the progression of microalbuminuria to overt renal disease, particularly in individuals with diabetes, HIV, and systemic inflammation. Integrating microalbuminuria screening into chronic disease management programs is essential to mitigate renal complications in these vulnerable groups.